An Analysis of Decorative Image Motifs for Grade VII-A of SMPN 18 Semarang (Coastal Eco-Culture-Based A Study of Creative Learning Outcomes) - adi, lukmono; Triyanto, Triyanto; Ibnan Syarif, Muh. (Universitas Negeri Semarang, 2021)
Coastal eco-culture- based learning of ornamental variety on is still very rarely to be carried out. This study aims to describe the visual form of decorative images for grade VII-A SMPN 18 Semarang, as a result of coastal eco-culture-based virtual creative learning during the Covid-19 pandemic. This study uses a qualitative method. The collecting data was conducted through observation, interviews, and documentation. The data transfer techniques was conducted through triangulation techniques. The data analysis was conducted through data reduction, data presentation, and drawing conclusions. Coastal eco-culture-based decorative images created by grade VII-A students of SMPN 18 Semarang were influenced by the natural and cultural aspects of the coastal areas typical of Semarang City. The form of decorative images namely Tugu Muda, Blenduk Church, Warak Ngendok, Blekok Srondol, marine life, typical coastal sea waves, there were even food motifs namely spring rolls. The colors used look bright which is identical to the typical color of the coast. In writing this article, the author identifies the visual elements of various shapes and colors decorated by students of grade VII-A SMPN 18 Semarang. Details of problems developed by adapting theory visual elements by Marvin Bartel, namely the analysis of visual elements of shapes and colors of motifs that are often used and emerged so that it became the initial identity of decorative motifs. So that the visualization resulting conclusions are in the form of basic shapes and colors that characterize decorative images of students in grade VII-A SMPN 18 Semarang, as a result of coastal eco-culture-based virtual creative learning. Furthermore, it can be concluded that the coastal eco-culture-based learning of decoration has positive implications in order to build creative capacity and cultural awareness of students.